2015
DOI: 10.1007/s00217-015-2490-2
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of dry-cured ham: a review. Part 1. Biochemical changes during the technological process

Abstract: various types of dry-cured ham are due to pig breed, feed of pigs, their weight and age, as well as differences in the production process. High-quality dry-cured hams, with a production length longer than 1 year, have distinct organoleptic characteristics: a rich, unique, and recognizable flavor and color in the range from rosy to maroon or brown red marbled with white fat. However, the sensorial, physical-chemical, aromatic, morphological, and textural characteristics of dry-cured ham vary significantly depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 78 publications
0
40
0
5
Order By: Relevance
“…Aldehydes are the primary contributors to the unique flavor of dry‐cured hams because of their rapid formation during lipid oxidation and low flavor thresholds (Pham et al, ). Alcohols and aldehydes are formed by the lipolytic and oxidative degradation of unsaturated fatty acids (Petrova et al, ). In this study, aldehydes, including both branched and linear aldehydes, were the most abundant group of volatile compounds during the processing of dry‐cured mutton ham (43.2%–49.88% of total volatile compounds).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aldehydes are the primary contributors to the unique flavor of dry‐cured hams because of their rapid formation during lipid oxidation and low flavor thresholds (Pham et al, ). Alcohols and aldehydes are formed by the lipolytic and oxidative degradation of unsaturated fatty acids (Petrova et al, ). In this study, aldehydes, including both branched and linear aldehydes, were the most abundant group of volatile compounds during the processing of dry‐cured mutton ham (43.2%–49.88% of total volatile compounds).…”
Section: Resultsmentioning
confidence: 99%
“…As a traditional food with broad consumer acceptance and unique local characteristics, dry‐cured ham represents the cultural heritage of a region. However, most dry‐cured hams in the market are made of pork (Harkouss et al, ; Martínez‐Arellano et al, ; Petrova, Aasen, Rustad, & Eikevik, ; Toldra, ). Mutton, a high‐protein, low‐fat, and low‐cholesterol meat, is expected to gain popularity as an alternative to pork in dry‐cured hams (Zhang, Yoo, Gathercole, Reis, & Farouk, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Santos‐Garces, Gou, Garcia‐Gil, Arnau, and Fulladosa () reported that the difference in the initial moisture contents of the Biceps femoris , Semimembranosus, and ST muscles is a factor affecting the drying rate of the dry‐cured meat products. In contrast, loss of moisture in production stages could vary due to the variance in salt intake at different ratios in different muscles (Petrova et al, ). In addition, it is known that the high connective tissue content of the ST muscle may affect the moisture loss of the product (Pietrasik, Aalhus, Gibson, & Shand, ).…”
Section: Resultsmentioning
confidence: 99%
“…While dry‐cured meat products that are processed in pieces vary by countries and regions, they are known as traditional foods worldwide (Petrova, Aasen, Rustad, & Elkevk, ). Pastırma, categorized in the group of intermediate moisture foods, is a traditional Turkish meat product which is obtained by curing, drying, paste (called çemen) seasoning, and re‐drying of the meat pieces obtained from certain parts of beef and water buffalo carcasses (Aksu & Kaya, ; Kaban, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation